Tráfico e porte de drogas para consumo pessoal: uma crítica aos critérios de distinção - Bora, Thais Rezende (2024)
The main objective of this study is to analyze why, to this day, uncertainty persists, especially in the legal environment, when classifying a conduct as drug trafficking or possession of drugs for personal consumption. To this end, the first chapter will deal with criminal drug policy, as well as alternative criminal policy, investigating not only the national context in which it is inserted, but also the criticisms and challenges faced. Subsequently, in the second chapter, the Brazilian antidrug legislative evolution is studied, covering the Republican Penal Code of 1890, Laws 6,368/1976, 10,409/2002, and 11,343/2006. In the third chapter, a detailed analysis of the Drug Law (Law 11,343/2006) is carried out, especially with regard to the criteria used by the legislator to distinguish drug dealers from drug users. At the end of this study, we intend to understand the legal uncertainty of operators of Brazilian law when classifying a conduct as drug trafficking or possession of drugs for personal consumption, as well as its effects on the Brazilian criminal execution system, given the social relevance of subject. Finally, this study proposes to offer a theoretically based contribution, as well as a guideline of forensic criteria that aims at a claim to justice, consistent with the search for getting closer to a fair result, which is what is desired with the Brazilian criminal system